Homogeneous dielectric elastomers with dramatically improved actuated strain by grafting dipoles onto SBS using thiol–ene click chemistry. Issue 24 (25th May 2016) - Sun, Haibin; Jiang, Chunyu; Ning, Nanying; Zhang, Liqun; Tian, Ming; Yuan, Shengli
Abstract : A simple, effective and controllable photochemical thiol–ene click reaction was used to dramatically improve the electromechanical properties of SBS. Abstract : Herein, we report an approach to the preparation of a homogeneous styrene–butadiene–styrene triblock copolymer (SBS) dielectric elastomer (DE) with dramatically improved actuated strain by using a photochemical thiol–ene click reaction. The stock SBS was grafted with dipoles (ester groups) to increase the polarizability of SBS. The grafting degree of dipoles on SBS can be controlled by irradiation time to control its electromechanical properties. The grafting degree of modified SBS increases with the increase of irradiation time, and a maximum grafting degree of 81% can be achieved at a radiation time of 40 min. After modification, the phase mixing of PB and PS blocks occurs and the size of PS domains largely decreases, leading to the obvious decrease in the tensile strength and elastic modulus ( Y ). However, the modified SBS still shows good tensile strength (>3 MPa). More importantly, the dielectric constant ( k ) largely increases for the modified SBS. The simultaneous increase in k and decrease in Y result in a large increase in electromechanical sensitivity, and thus a large increase in maximum actuated strain and the actuated strain at low electric fields ( e.g. 15 kV mm −1 ). In addition, the modified SBS shows consistently low dielectric loss. Our study provides a simple, effective and controllable chemical method to prepare a homogeneous DE with a high k, large actuated strain at a low electric field, good mechanical strength, easy processibility, and recyclability.